CSR and job satisfaction: Role of CSR importance to employee and procedural justice. Issue 4 (2nd October 2021) - Murshed, Feisal; Sen, Sandipan; Savitskie, Katrina; Xu, Hangjun
ABSTRACT: This research develops and empirically validates a model that examines how employees' perceptions of a firm's corporate social responsibility (CSR) commitment, specifically, social CSR and environmental CSR, may influence job satisfaction, as mediated by CSR importance to employee. In addition, we demonstrate that this mediation effect varies according to the level of procedural justice. Analyses of survey data collected from 264 employees find support for the hypotheses. Notably, the interactive effect of procedural justice and environmental CSR turns out to be negative. This research contributes to the emerging CSR-related literature in marketing and provides new insights into the justice-CSR interface.